Integrated receivers with bottom subcooling for automotive air conditioning: Detailed experimental study of their filling capacity. (February 2016) - Cola, F.; De Gennaro, M.; Perocchio, D.; Canuto, E.; Daniele, S.; Napoli, P.; Toscano Rivalta, G.; Chiavazzo, E.; Fasano, M.; Asinari, P.
Highlights: Novel design strategy for integrated receivers in automotive air conditioning. Receiver diameter and axial spacing are the most influential parameters. Systematic experimental campaign built using design of experiments. Abstract: The use of the integrated receiver in condensers for common automotive air conditioning – A/C – systems is widespread, because of its thermodynamic and operational advantages. Many studies have been already conducted on estimating the effect of the subcooling value. However, this study aims at determining the most important factors affecting the length of the refrigerant stable operating plateau and how the receiver filling is affected by geometrical and thermodynamic boundary conditions, by means of an experimental campaign built using design of experiments – DOE – techniques. Results demonstrate how the receiver diameter and the axial spacing between its inlet and outlet holes have the highest influence on the receiver operation. Finally, these results have been used to set up a numerical model able to accurately estimate the filling efficiency of the integrated receiver, in terms of volume of the operating plateau compared to the net available receiver volume.